KONSEP PENGEMBANGAN KEBIASAAN BELAJAR di ERA INDUSTRI 4.0 - Sakwa Kholdun (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
As a guidance and counseling teacher, of course, has the task of helping students overcome these problems by identifying learning problems experienced by students, analyzing these problems appropriately, offering learning style solutions or solutions to students solving these learning problems. The point is that students are able to be independent in learning. The results of research conducted by researchers using the DCM questionnaire (Checklist of Problems) to 31 students of class X IIK 2 in MAN 3 Bantul get the highest problem is the problem of study habits. In the aspect of the problem of study habits, the highest item that becomes a problem is irregular learning time, if learning is often sleepy, studying only at night, studying when there are tests, and often feeling lazy to learn. Bk teachers need to make a description of what needs are given to students, how their goals, alternative service and what kind of evaluation to be given to students. Based on the results of the study it has been presented that it is known that students need help providing effective tutoring services that can affect the learning habits of students of class X IIK.